Effect of magnetic field on microhardness of germanium - Makara, V.A.; Steblenko, L.P.; Kuryliuk, A.M.; Naumenko, S.M.; Kolchenko, Iu.L.; Kravchenko, V.M. (Functional Materials, 2007)
Microhardness variations in germanium crystals caused by a weak constant magnetic field have been studied. It is fount that the magnetomechanical effect, that is relative change in microhardness, becomes relaxed in time. The results obtained indicate that the effect physical nature is related to spin-depentent reactions in the subsystem of point defects.